The Caspase Inhibitor Z-VAD-FMK Alleviates Endotoxic Shock via Inducing Macrophages Necroptosis and Promoting MDSCs-Mediated Inhibition of Macrophages Activation - Li, Xuehui; Yao, Xiaoying; Zhu, Yuzhen; Zhang, Hui; Wang, Haiyan; Ma, Qun; Yan, Fenglian; Yang, Yonghong; Zhang, Junfeng; Shi, Hui; Ning, Zhaochen; Dai, Jun; et al. (Frontiers in Immunology, 2019)
Macrophages play a critical role in the pathogenesis of endotoxin shock by producing excessive amounts of pro-inflammatory cytokines. A pan-caspase inhibitor, zVAD, can be used to induce necroptosis under certain stimuli. The role of zVAD in both regulating the survival and activation of macrophages, and the pathogenesis of endotoxin shock remains not entirely clear. Here, we found that treatment of mice with zVAD could significantly reduce mortality and alleviate disease after lipopolysaccharide (LPS) challenge. Notably, in LPS-challenged mice, treatment with zVAD could also reduce the percentage of peritoneal macrophages by promoting necroptosis and inhibiting pro-inflammatory responses in macrophages. In vitro studies showed that pretreatment with zVAD promoted LPS-induced nitric oxide-mediated necroptosis of bone marrow-derived macrophages (BMDMs), leading to reduced pro-inflammatory cytokine secretion. Interestingly, zVAD treatment promoted the accumulation of myeloid-derived suppressor cells (MDSCs) in a mouse model of endotoxin shock, and this process inhibited LPS-induced pro-inflammatory responses in macrophages. Based on these findings, we conclude that treatment with zVAD alleviates LPS-induced endotoxic shock by inducing macrophage necroptosis and promoting MDSC-mediated inhibition of macrophage activation. Thus, this study provides insights into the effects of zVAD treatment in inflammatory diseases, especially endotoxic shock.